Development of an Online-Based Islamic Education Management System in Islamic Primary Education Institutions - Supriatna, Dasep (Journal of Asian Primary Education (JoAPE), 2025)
This study aims to explore the development and application of online-based Islamic education management system as a means of Education modernization while maintaining the core values of Islamic ethics. Using a descriptive qualitative approach, this study analyzes various aspects of the system, including digital integration, operational efficiency in the environment of Islamic basic education institutions, and structured feedback mechanisms for continuous improvement. The Data was collected through literature review, content analysis of related documents, and observation of global best practices in Islamic education technology. These findings suggest that online systems effectively streamline processes such as curriculum management, student services, and resource allocation, while improving access to spiritual and academic content. In addition, the platform supports interactive learning, cross-cultural collaboration, and adaptation to global trends such as artificial intelligence, virtual reality, and blockchain technology. The study also highlights the importance of participatory feedback mechanisms to ensure user-friendliness, relevance, and alignment with Islamic principles. Implementation recommendations include capacity building initiatives, global collaboration, and regular ethical evaluations to ensure the sustainability and effectiveness of these systems in the context of modern Islamic education.